1999
DOI: 10.2169/internalmedicine.38.315
|View full text |Cite
|
Sign up to set email alerts
|

What Have We Learned from Gene Targeting Studies for the Renin Angiotensin System of the Kidney?

Abstract: Over the last decade, gene targeting technologies have provided investigators with powerful new tools to study the physiology and pathophysiology of the kidney. In that, the renin-angiotensin system (RAS) has been a subject of intense investigation. Detailed analyses of mutant mice have not only confirmed notions already suggested by other studies, but also shed a new light on previously unrecognized functions of RAS.In this review, wewill focus on what wehave learned from these gene targeted animals in partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 59 publications
(45 reference statements)
0
13
0
Order By: Relevance
“…The direct actions of angiotensin II in the kidney include an increase in tubular sodium reabsorption and an influence on glomerular filtration rate (GFR), but morphopathological changes such as accumulation of extracellular matrix and mesangial cell proliferation and hypertrophy 17,18 are of more importance for the pathogenesis of renal impairment. Therefore, the question has arisen as to whether pharmacological intervention in the RAS confers an additional benefit beyond the lowering of blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The direct actions of angiotensin II in the kidney include an increase in tubular sodium reabsorption and an influence on glomerular filtration rate (GFR), but morphopathological changes such as accumulation of extracellular matrix and mesangial cell proliferation and hypertrophy 17,18 are of more importance for the pathogenesis of renal impairment. Therefore, the question has arisen as to whether pharmacological intervention in the RAS confers an additional benefit beyond the lowering of blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has become evident that a functional RAS is required for normal mammalian renal development. 1 Renin, an aspartyl protease, initiates an enzymatic cascade that results in the production of the vasoactive peptide angiotensin II, the major effector molecule of the RAS. Transcription of renin genes is tissuespecifically and developmentally regulated.…”
mentioning
confidence: 99%
“…Additionally, the reninangiotensin system has been implicated in aspects of renal development by the observation that pharmacological and genetic disruptions of renin-angiotensin system function result in aberrant renal morphology (for reviews, see Refs. [2][3][4].…”
mentioning
confidence: 99%
“…The PPE was shown to bind As4.1 cell nuclear proteins in electrophoretic mobility shift assays (EMSAs). Further competition assays indicated that the minimal sequence required for protein binding included N (1)(2)(3) TAATAAATCA. Mutation of the PPE in the Ren-CAT construct containing a 4.1-kb mouse renin sequence dramatically reduced the chloramphenicol acetyltransferase activity in transfection assays suggesting a critical role of this element in the regulation of mouse renin gene expression.…”
mentioning
confidence: 99%